A Multimodal Discourse Analysis of the Endangered Tigers in WWF Posters - Sukma, Annisa Indah; Asidiky, Zakie; Agustian, Agung Farid (Universitas Sanata Dharma, 2023)
This Multimodal Discourse Analysis (MDA) research examined World Wildlife Fund for Nature (WWF) posters campaigning for tiger protection, whose population has been fewer than 5000 in recent years. It uses a qualitative descriptive method with Kress and van Leeuwen's compositional meaning theory (2006) to explore how the composition of the posters delivered messages to readers. Besides, it also tried to reveal the ideologies depicted in those posters critically. The number of data analyzed was 6 (six) tiger posters taken from the adsoftheworld website (https://www.adsoftheworld.com) with the keywords 'tiger' and 'WWF.' As a result, the salient elements of the selected posters represented a critical state of the tiger population. They could also convey to readers that the extinction of tigers can be prevented with a wise life. In addition, both verbal and visual elements depicted several ideologies: (1) the tiger was seen as property, not as a living creature, (2) people could choose to fight for or destroy the tiger, (3) power hierarchy made people unable to act, and (4) the tigers are in endangered states. Hopefully, this research can be used as a theoretical reference for further research on environmental and animal issues in the multimodal field. Besides, visual communication practitioners can imitate or follow the analyzed posters in this research to make any content concerning any life issues by paying more attention to the salient elements in their posters.